Senjang Budaya (Cultural Differences) Sosio-Ekonomi Antar Etnis Umat MAHK Kabupaten Minahasa Utara - Sepang, Alfriets (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
The Seventh-day Adventist church believes that diversity is God’s desire.  Every member of the church believes that as Christ’s follower, ethnic group, race, tribe, language, or/and skin color differences are not really important because every person came from the same ancestor. According to Morales and Gudmundsson: “diversity, then, is a divine gift, not only in our male and female human condition, but also in our personalities and viewpoints, our talents and gifts.”  Ten social factors that are used by the researcher as basis for the questionnaire are diversity, faith maturity, salvation is from God, truth, doctrines, other people’s cultural evaluation, respect toward other ethnic group’s culture, norm, tolerance and integration with other ethnic groups. The analysis result shows that Toutemboan ethnic strongly agree that the ten social factors that are used by the researcher affect the cultural differences in the Seventh-day Adventist church in Kabupaten Minahasa Utara.  Whereas the Tombulu ethnic strongly agree only with the two variables that are used by the researcher. The Pasan ethnic and other ethnic groups strongly agree with four social variables that affect the cultural differences. From 329 respondents, there are 201 respondents who strongly agree, 103 respondents who agree, 17 respondents who are uncertain, 6 respondents who disagree, and 3 respondents who strongly disagree that diversity comes from God. Based on ANOVA analysis, F test at a level of significance of 0.004 and with Df of 10, then variables that used by the researcher has a significant effect in solving the cultural differences in the Seventh-day Adventish church in Kabupaten Minahasa Utara.